Energy purchase schemes of railway carriers in times of crisis on global energy and fuel markets - Alan Beroud (Przegląd Komunikacyjny)
Abstract: The paper outlines energy purchase schemes for railway carriers, in a particularly difficult situation on the energy and fuel market. The National Power System was described and the dependence of forward prices of electricity on the prices of energy raw materials, i.e. natural gas, coal, CO2 emission allowances. An analysis of the impact of the geopolitical situation on the energy and fuel markets was also undertaken. It was also explained how electricity contracting schemes operate on the basis of the Energy Law.